2011
DOI: 10.1002/jbmr.531
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human osteoclast development by dendritic cell-specific transmembrane protein (DC-STAMP)

Abstract: Osteoclasts (OC) are bone-resorbing, multinucleated cells that are generated via fusion of OC precursors (OCP). The frequency of OCP is elevated in patients with erosive inflammatory arthritis and metabolic bone diseases. Although many cytokines and cell surface receptors are known to participate in osteoclastogenesis, the molecular mechanisms underlying the regulation of this cellular transformation are poorly understood. Herein, we focused our studies on the dendritic cell-specific transmembrane protein (DC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
122
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 47 publications
5
122
0
1
Order By: Relevance
“…Because DC-STAMP is known to be involved in the fusion of osteoclast precursors (42, 46 -48), the change could be linked functionally to the reduction in multinuclear and giant cells detected in enoxacintreated cultures. Levels of cell surface DC-STAMP have been shown to gradually decline during osteoclastogenesis (49). These results indicate that enoxacin influences DC-STAMP toward a cell surface expression pattern of DC-STAMP associated with less mature osteoclasts.…”
Section: Discussionmentioning
confidence: 84%
“…Because DC-STAMP is known to be involved in the fusion of osteoclast precursors (42, 46 -48), the change could be linked functionally to the reduction in multinuclear and giant cells detected in enoxacintreated cultures. Levels of cell surface DC-STAMP have been shown to gradually decline during osteoclastogenesis (49). These results indicate that enoxacin influences DC-STAMP toward a cell surface expression pattern of DC-STAMP associated with less mature osteoclasts.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous molecular factors have been identified over the years, which primarily play a major role in the preparative steps required for fusion. The most prominent of these is DC‐STAMP (dendritic cell‐specific transmembrane protein) (Kukita et al, 2004; Yagi et al, 2005; Iwasaki et al, 2008; Mensah et al, 2010; Chiu et al, 2012; Chiu and Ritchlin, 2016), which has been identified as one of the most essential single factors supporting both differentiation and fusion. However, also other factors such as CD47 (Han et al, 2000; Lundberg et al, 2007; Maile et al, 2011; Koskinen et al, 2013; Hobolt‐Pedersen et al, 2014), syncytin‐1 (Soe et al, 2011), OC‐STAMP (osteoclast stimulatory transmembrane protein) (Miyamoto et al, 2012; Witwicka et al, 2015), dynamin (Shin et al, 2014; Verma et al, 2014), Pin1 (peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1) (Islam et al, 2014; Cho et al, 2015), and e‐cadherin (Mbalaviele et al, 1995; Fiorino and Harrison, 2016) are involved in OC fusion, but it is important to stress that this list is not exhaustive.…”
mentioning
confidence: 99%
“…Bone-resorbing activity of mononuclear osteoclasts is lower than that of multinucleated osteoclasts (Yagi et al, 2005;Miyamoto, 2011;Chiu et al, 2012). In addition, TRAP activities in multinucleated osteoclastic giant cells of medium size are size-dependent, and the large cells reveal, in part, low activities (Metze et al, 1987).…”
Section: Discussionmentioning
confidence: 96%